High‐Efficiency (LixCu1−x)2ZnSn(S, Se)4 Kesterite Solar Cells with Lithium Alloying. Issue 34 (16th October 2018) - Cabas‐Vidani, Antonio; Haass, Stefan G.; Andres, Christian; Caballero, Raquel; Figi, Renato; Schreiner, Claudia; Márquez, José A.; Hages, Charles; Unold, Thomas; Bleiner, Davide; Tiwari, Ayodhya N.; Romanyuk, Yaroslav E.
Abstract: The performance‐boosting effect of alkali treatments is well known for chalcogenide thin‐film solar cells based on Cu(In, Ga)Se2 (CIGS) and Cu2 ZnSn(S, Se)4 (CZTSSe–kesterite) absorbers. In contrast to heavier alkali elements, lithium is expected to alloy with the kesterite phase leading to the solid solution (Li x Cu1− x )2 ZnSn(S, Se)4 (LCZTSSe), which offers a way of tuning the semiconductor bandgap by changing the ratio Li/(Li+Cu). Here is presented an experimental series of solution‐processed LCZTSSe with lithium fraction Li/(Li+Cu) ranging from x = 0 to 0.12 in the selenized absorber as measured by means of inductively coupled plasma mass spectrometry. The proportional increase in lattice parameter a and bandgap from 1.05 to 1.18 eV confirms the lithium alloying in the kesterite phase. Increase in grain size is observed for x up to 0.07, whereas a higher lithium fraction leads to a porous absorber morphology due to an inhomogeneous distribution of Li‐containing compounds in the kesterite layer. An increase of the photoluminescence quantum yield is observed as the Li fraction increases in the absorber layer. A champion device exhibits a remarkable efficiency of 11.6% (12.2% active area) for x = 0.06, close to the world record value of 12.6% demonstrating the effectiveness of lithium alloying. Abstract : In contrast to the other alkali elements, Li can alloy in the mixed (Li x Cu1− x )2 ZnSn(S, Se)4 kesterite phase by substituting for Cu, hence widening the bandgap. For an optimal Li fraction of Li/(Li+Cu) = 0.06, a solar cell with a maximum efficiency of 11.6% (illuminated area) is obtained.